Assets Accounting Systems: A Literature Review - Ghusny Damayanti; Yusri Hazmi; Vanessa Ocha Rachman; Riska Vebriyanti (North Press, 2024)
The inventory accounting system can be done in two ways, namely manually and with a computerized system. Inventory accounting system manually and by method physically counts the goods in the warehouse and then makes a report on the remaining inventory. while the inventory accounting system is computerized so the recording is carried out by entering data on goods that have been sold and goods that have been purchased into the computer system, then the computer will automatically reduce the inventory data available with data on goods that have been sold. The inventory accounting system aims to record mutations for each type of inventory stored in the warehouse. This system is closely related to the sales system, sales returns system, purchasing system, purchase returns system, and production cost accounting system. Inventory of finished products Accounting System Transactions Relevant Systems and Procedures Finished products produced Sales returns Procedure for recording the cost of finished products Procedure for recording the cost of finished products sold Procedure for recording the cost of finished products received back from buyer’s Physical inventory counting system Physical inventory count.